Influencing Factors on Customer Behavioral Intentions to Use a Food Delivery App: A Study of GrabFood in Malaysia - Lok, Yee Huei; Teoh, Kok Ban; Liou, Zi Yao; Lim, Jin Ting; Lim, Kai En; Lim, Pei En; Kee, Daisy Mui Hung (The Global Academia Publisher, 2024)
Digital technology has revolutionized the food and beverage industry, leading to a rapid expansion of food delivery services. GrabFood has become a popular option for individuals seeking simple and convenient food delivery services, particularly among university students. This study investigates the factors influencing GrabFood’s adoption, using a combination of primary and secondary data. An online survey of 150 respondents highlighted key trends in customer behavior, identifying perceived usefulness, perceived convenience, and perceived quality of service as key determinants of user intentions. This research introduces customer satisfaction as an intermediary variable significantly influencing the relationship between the perceived attributes and behavioral intentions. These factors significantly impact the decision-making process, highlighting the importance of app efficiency and service quality in Malaysia's competitive food delivery industry. The findings underscore the need to enhance customer engagement and refine service strategies, which might be beneficial in the evolving digital food service sector